2018
DOI: 10.1542/hpeds.2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Sexual History in Hospitalized Adolescents on the General Pediatrics Service

Abstract: Sexual history taking does not occur universally for hospitalized adolescents. Girls were screened more often than boys despite similar rates of sexual activity. The inpatient admission may be a missed opportunity for harm-reduction counseling and adherence to sexually transmitted infection testing guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…15 Further, despite recommendations to routinely perform a confidential sexual health history in adolescents, 2,3 pediatricians are not consistently providing this critical evidence-based care in the ambulatory or hospital-based setting. 4,16 A recent study in the pediatric hospital demonstrated only 62% of adolescents have a documented sexual history. 16 National guidelines recommend at a minimum: annual GC/CT screening for all sexually active females <25 years of age, HIV testing at least once for ages 13–64 in all health care settings, and additional risk-based screening for high risk populations such as patients with multiple partners, gay and bisexual patients, and men who have sex with men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Further, despite recommendations to routinely perform a confidential sexual health history in adolescents, 2,3 pediatricians are not consistently providing this critical evidence-based care in the ambulatory or hospital-based setting. 4,16 A recent study in the pediatric hospital demonstrated only 62% of adolescents have a documented sexual history. 16 National guidelines recommend at a minimum: annual GC/CT screening for all sexually active females <25 years of age, HIV testing at least once for ages 13–64 in all health care settings, and additional risk-based screening for high risk populations such as patients with multiple partners, gay and bisexual patients, and men who have sex with men.…”
Section: Discussionmentioning
confidence: 99%
“…4,16 A recent study in the pediatric hospital demonstrated only 62% of adolescents have a documented sexual history. 16 National guidelines recommend at a minimum: annual GC/CT screening for all sexually active females <25 years of age, HIV testing at least once for ages 13–64 in all health care settings, and additional risk-based screening for high risk populations such as patients with multiple partners, gay and bisexual patients, and men who have sex with men. 1,17 We found females were more likely to be tested than males.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 While social and sexual history taking is a cornerstone of the patient interview, providers often fail to adequately document their patient's self-reported SBDH. [10][11][12][13][14] In addition, low adoption rates for clinical screening tools for SBDH in EHRs exist as a barrier to the collection of this information in a usable format. 9,15 While the majority of documentation related to SBDH exists in free-text notes, information on SBDH is also manifest in the structured data elements such as diagnosis codes and laboratory tests.…”
Section: Background and Significancementioning
confidence: 99%
“…14 Although many adolescents who are hospitalized are at an increased risk for pregnancy complications due to their underlying medical conditions or use of teratogenic medication, sexual risk assessment is not consistently performed in this setting. 15,16 Although adolescents and their parents are supportive of sexual health discussions, STI testing, and pregnancy prevention education in the inpatient setting, 17 a thorough understanding of factors that influence the provision of this care among pediatric hospital physicians is lacking. This formative information is needed to facilitate efforts to improve and standardize clinical care provision.…”
mentioning
confidence: 99%